MBSE APPROACH FOR FACILITATING THE APPLICATION OF STANDARDS IN THE VEHICLE DEVELOPMENT PROCESS - Angeleska, Elena; Changoski, Vasko; Rizov, Tasko; Sidorenko, S (Faculty of Engineering, University of Kragujevac, 2023)
The development of complex vehicle systems that integrate latest trends and user needs with regulations, standards, and engineering requirements needs to rely on a strong multi-disciplinary collaboration between experts who exchange information from all relevant fields included in the vehicle development process. Constantly following, updating and applying the input information from various sources when working on vehicle systems can be a daunting task. The Model-Based Systems Engineering (MBSE) approach can provide a strategy for easier coping with the complexity of vehicle systems. This is extremely beneficial since it helps to create an information base where the information is represented in an integrated and consistent system model rather than in isolated documents. This paper presents a concept of an information platform based on MBSE. The goal of the platform is to become an engineering tool for incorporating all relevant data (requirements, standards, regulations) in a manner that they can be directly linked to the adequate system components, simple to interpret and be used by all members of the development team. The purpose of this platform is to: (1) facilitate the development process and interdisciplinary collaboration; (2) help to follow regulations correctly and avoid mistakes; and (3) keep all project data systematized.
Keywords: Vehicle Design, Platform, MBSE, Regulations